2019
DOI: 10.1128/jvi.01510-18
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Poliovirus Capsid Mutant with Enhanced Thermal Stability

Abstract: Enteric viruses, including poliovirus, are spread by the fecal-oral route. In order to persist and transmit to a new host, enteric virus particles must remain stable once they are in the environment. Environmental stressors such as heat and disinfectants can inactivate virus particles and prevent viral transmission. It has been previously demonstrated that bacteria or bacterial surface glycans can enhance poliovirus virion stability and limit inactivation from heat or bleach. While investigating the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 19 publications
(36 reference statements)
6
24
0
Order By: Relevance
“…3C and E). We also demonstrated that PV-M132V was stable during 8 days of incubation at 37°C in both PBS and feces (13). Interestingly, mengovirus exhibited significant inactivation after 4 days at 37°C, but incubation in feces limited this inactivation (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…3C and E). We also demonstrated that PV-M132V was stable during 8 days of incubation at 37°C in both PBS and feces (13). Interestingly, mengovirus exhibited significant inactivation after 4 days at 37°C, but incubation in feces limited this inactivation (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…1B and Table 1). Additionally, our panel included a PV mutant with a single amino acid change in the VP1 capsid coding region (PV-M132V), which confers enhanced thermal stability in the absence of bacteria (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such directed evolution experiments, virus populations are grown under conditions that favor either the emergence or further optimization of the desired phenotype. For example, this process has been used to obtain live attenuated vaccines for numerous viruses by repeated growth at suboptimal conditions 3 , improving in vivo models by serial infection of the desired host 4-9 , isolating RNA viruses with high-fidelity polymerases by growth under condition of increased mutational load 10,11 , selection of viruses with improved oncolytic properties [12][13][14] , or isolation of viruses and virus-like particles of increased stability [15][16][17] . To date, these studies have relied upon the natural mutational processes of RNA viruses to generate the diversity upon which selection is applied.…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to assume that the initial rotation, as well as the structural disruptions, may be inhibited by stronger interaction forces at the subunit interfaces. Experimental evolution experiments have shown that thermostable poliovirus variants carry mutations in the hydrophobic pocket region of VP1 (20)(21)(22). These mutations are distant from the pentameric interfaces but close to the interface of the protomeric subunits.…”
mentioning
confidence: 99%